A Didactic Design Experiment - towards a network society learning paradigm - Karin Tweddell Levinsen (Stockholm University Press, 2009)
The ongoing transition from industrial to network society challenges educational practices and the process is characterised by opposing forces. At the political level, New Public Management initiatives oppose the general consensus that it is necessary to consolidate network society competencies. At the level of everyday educational practice we see a mounting tension between the quality of educational outcomes, in terms of genuine learning, and students' strategies for dealing with an increasing pressure of efficiency and time. This article presents a design for teaching and learning experiment that aims to navigate these turbulent waters, scaffold genuine learning, satisfy learning objectives and ease the strain on students. Due to the experiences and knowledge derived from the experiment, the paper argues that the model behind the experiment demonstrates qualities that may be developed and refined and contribute to the educational system's adjustment to the network society.